The role of subnational tax capacity: A path toward regional integration - César Vega Zárate; Leticia Murcia López (Public and Municipal Finance, 2025)
The tax capacity exercised by subnational governments in a country is fundamental in shaping the tax and economic system, especially when there is a coordination of interests, such as in the Pacific Alliance. Therefore, the coordination exercised by its member countries – Chile, Colombia, Mexico, and Peru – must be strategically aligned to comprehensively strengthen this Alliance. Considering the above, the objective of this study is to identify the similarities or differences between these four countries, check the tax behaviors of their subnational governments, and assess the degree of their impact on this trade agreement. Based on a longitudinal quantitative methodology, the results reveal significant differences between the subnational collection systems, identifying that Mexico and Peru are the only members that have maintained a similar trend, significantly differentiating themselves from Chile and Colombia. Despite their subnational tax structures, the main finding is that the Pacific Alliance needs to implement more coordinated actions in tax matters to strengthen its economic activities with other countries. A lack of coordination could counteract the commercial and financial strategies presented as a regional bloc, impacting investment, competitiveness, and regional sustainability. Overall, coordinated tax policies within the Pacific Alliance can drive regional integration, contributing to the region’s long-term stability.